2018
DOI: 10.1063/1.5021172
|View full text |Cite
|
Sign up to set email alerts
|

Direct writing of room temperature and zero field skyrmion lattices by a scanning local magnetic field

Abstract: Magnetic skyrmions are topologically protected nanoscale spin textures exhibiting fascinating physical behaviors. Recent observations of room temperature skyrmions in sputtered multilayer films are an important step towards their use in ultra-low power devices. Such practical applications prefer skyrmions to be stable at zero magnetic fields and room temperature. Here, we report the creation of skyrmion lattices in Pt/Co/Ta multilayers by a scanning local field using magnetic force microscopy tips. We also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 48 publications
(71 reference statements)
4
75
0
Order By: Relevance
“…While MFM is well established as a tool to measure DMI and investigate nanoscale magnetic skyrmions in Co-based multilayer stacks 17,42,[44][45][46] , similar studies for CoFeB-based systems have involved using less widely available techniques, such as Scanning Transmission X-ray Microscopy (STXM) 16,18,26,27 , Magnetic Transmission soft X-ray Microscopy (MTXM) 16,19 or X-ray holography 25 . MFM imaging of soft magnetic materials like CoFeB can actually be very challenging due to image deformations caused by the probe-sample magnetic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…While MFM is well established as a tool to measure DMI and investigate nanoscale magnetic skyrmions in Co-based multilayer stacks 17,42,[44][45][46] , similar studies for CoFeB-based systems have involved using less widely available techniques, such as Scanning Transmission X-ray Microscopy (STXM) 16,18,26,27 , Magnetic Transmission soft X-ray Microscopy (MTXM) 16,19 or X-ray holography 25 . MFM imaging of soft magnetic materials like CoFeB can actually be very challenging due to image deformations caused by the probe-sample magnetic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Small skyrmions can be also written and deleted in a controlled fashion with local spin-polarized currents from a scanning tunneling microscope 59 . With a tip of a scanning magnetic force microscope (MFM), one can cut stripe magnetic domains into skyrmions 60 . It has been suggested that individual skyrmions can also be written with an MFM tip 61 .…”
Section: Introductionmentioning
confidence: 99%
“…Such kind of fields can be, obviously, created in other ways. For example, the stray fields of radial symmetry can be created by the tip of a magnetic force microscope, resulting in the observation of unconventional vortices in soft magnetic dots, which, however, disappear as soon as the tip is removed [45][46][47].…”
Section: Nanostructures Under Study and Unconventional Magnetizatmentioning
confidence: 99%